An action research on Music Activities in Rhythmic for Early Childhood Development - Raveechatphong, Kittiya; Chatphong, Ratthanin; Phetmunin , Rittichut (Journal for Developing the Social and Community, 2024)
The objective of this research aim to teach music rhythm and movement to early childhood children. That is an important period for learning basic skills. Which should be training and cultivation To stimulate brain development to be highly effective. The purpose of this research is to study teaching management. using music rhythm and movement activities including learning of Western music rhythms. By having early childhood children move with the music rhythm, including counting with the rhythm of the quarter notes. and with the rhythm of the eighth notes. Practice skills for develop music rhythm and movement activities which researcher created for prepare and develop the early childhood of body, feeling, social and IQ. The population was 1 room of the early childhood in “Saint Joseph Sriphetchabun School”, The early childhood students will learn with using rhythmic games and music which enhances the emotional aesthetics. The results of this research are part of the research project of music activities on rhythm for early childhood development. Faculty of Humanities and Social Sciences Phetchabun Rajabhat University.